2013
DOI: 10.1073/pnas.1308595110
|View full text |Cite
|
Sign up to set email alerts
|

DNA conformations in mismatch repair probed in solution by X-ray scattering from gold nanocrystals

Abstract: DNA metabolism and processing frequently require transient or metastable DNA conformations that are biologically important but challenging to characterize. We use gold nanocrystal labels combined with small angle X-ray scattering to develop, test, and apply a method to follow DNA conformations acting in the Escherichia coli mismatch repair (MMR) system in solution. We developed a neutral PEG linker that allowed gold-labeled DNAs to be flashcooled and stored without degradation in sample quality. The 1,000-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 55 publications
2
61
0
Order By: Relevance
“…This latter finding provides an explanation for the observation that yMutLα can interact with an ATPasesite mutant of yMutSα that does not form a sliding clamp (30). Interestingly, a recent study monitoring DNA bending with small angle X-ray scattering in solution (31), suggests that, for E. coli proteins, MutL interacts with MutS after an ATP-dependent conformational change from a bent DNA state to an unbent DNA state. If E. coli and Taq MMR follow the same pathway (discussed later in Conclusions), then extrapolating this result suggests that our FRET 0.45 state (between protein and DNA) involves unbent DNA (Fig.…”
Section: Intermediate Steps During Assembly Of Muts-mutl Complexesmentioning
confidence: 89%
“…This latter finding provides an explanation for the observation that yMutLα can interact with an ATPasesite mutant of yMutSα that does not form a sliding clamp (30). Interestingly, a recent study monitoring DNA bending with small angle X-ray scattering in solution (31), suggests that, for E. coli proteins, MutL interacts with MutS after an ATP-dependent conformational change from a bent DNA state to an unbent DNA state. If E. coli and Taq MMR follow the same pathway (discussed later in Conclusions), then extrapolating this result suggests that our FRET 0.45 state (between protein and DNA) involves unbent DNA (Fig.…”
Section: Intermediate Steps During Assembly Of Muts-mutl Complexesmentioning
confidence: 89%
“…X-ray interferometry readily provides information about translational displacements, which are difficult to assess with RDC measurements (47), as well as angular movements, and it is more straightforward to extend to larger structures (22,24) and other classes of macromolecules. However, X-ray interferometry is limited in detecting rare conformers (17,18,23) so that techniques that can trap or assess rare excursions, such as NMR relaxation dispersion (48), paramagnetic relaxation enhancement (49), hydrogen/deuterium exchange (50), and cyclization (51), are powerful complements to X-ray interferometry.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray interferometry can be used to determine site-tosite distance distributions instantaneously because it relies on atomic scattering (17,(19)(20)(21)(22)(23)(24). Standard small-angle X-ray scattering (SAXS) measures the sum of the scattering and scattering interference from all atoms in a macromolecule (25).…”
Section: Helix-junction-helix | Saxsmentioning
confidence: 99%
“…On the other hand, the sliding clamp model proposes that the mispair is recognized by an ADP-bound MutS, resulting in a rapid ADP-ATP exchange and a MutS conformational change that releases MutS from the mismatch allowing MutS to diffuse along the DNA backbone as a sliding clamp, in an ATP-hydrolysis-independent manner (Acharya et al 2003; Gradia et al 1999; Hura et al 2013; Lee et al 2014; Mendillo et al 2005). DXMS studies have revealed some of these ATP binding induced conformational changes (Mendillo et al 2010).…”
Section: Atpase Domainmentioning
confidence: 99%